Groups Effect of Types 5 D and 5 Î‘ on The Points of Projective Plane Over 31 ,29,F =qq - Al-Zangana, Emad B. A. K. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The purpose of this paper is  to find an arc of degree five in 31 ,29),(2, =qqPG , with stabilizer group of type dihedral group of degree five 5 D and arcs of degree six and ten with stabilizer groups of type alternating group of degree five 5 A ,  then study the effect of  5 D and 5A on the points of projective plane. Also, find a pentastigm which has collinear diagonal points.